The Aesthetics of Sand: Reclaiming Hong Kong's Unsettled Grounds. Issue 2 (1st December 2021) - Brigstocke, Julian
Abstract : Sand is a key material foundation of modern cities. In Hong Kong, a city founded in British mercantile imperialism, the extraction of sand needed for construction and reclamation projects has always been tied up with violent dispossession. Experimenting with the forms and poetics of postcolonial and new materialist critical theory, and thinking with sand's distinctive materialities and forms of drift, this paper develops a speculative critique of Hong Kong's sandy infrastructure. Hong Kong's colonial and post-colonial authority is legitimized by a continual process of surfacing and resurfacing, claiming and reclaiming. By evoking the process of saltation, one of sand's distinctive mechanisms of movement, the paper uncovers utopian potential in sand's unsettled qualities, searching for a new ethics of ground-down grounds.